2008
DOI: 10.1007/s10531-008-9502-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing tree diversity and composition in coffee farms and sacred forests in the Western Ghats of India

Abstract: Expansion of coffee cultivation is one of the causes of deforestation and biodiversity loss. However, shade grown coffee has been promoted as a means for preserving biodiversity in the tropics. In this study we compared tree diversity in two types of coffee management regimes with the sacred groves in the Western Ghats of India. We computed species accumulation curves, species diversity indices and evenness indices to compare the different management regimes. Results of diversity indices showed that shade coff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…On the other hand, studies that have examined tree biodiversity in agroforestry systems have found higher levels of tree biodiversity in the more rustic, less intensively managed agroforests (Moguel and Toledo 1999, Reynoso 2004, López-Gómez et al 2008, Asase et al 2010) and shifts in tree species community composition in agroforests as compared to forests (Ambinakudige and Sathish 2008, Anglaaere et al 2011, Valencia et al 2014. Studies have also found that pioneer trees tend to dominate agroforestry systems (Rolim and Chiarello 2004, Bandeira et al 2005, Valencia et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies that have examined tree biodiversity in agroforestry systems have found higher levels of tree biodiversity in the more rustic, less intensively managed agroforests (Moguel and Toledo 1999, Reynoso 2004, López-Gómez et al 2008, Asase et al 2010) and shifts in tree species community composition in agroforests as compared to forests (Ambinakudige and Sathish 2008, Anglaaere et al 2011, Valencia et al 2014. Studies have also found that pioneer trees tend to dominate agroforestry systems (Rolim and Chiarello 2004, Bandeira et al 2005, Valencia et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rice was replaced with a more beneficial ginger crop in rice paddies. Finally, extension of coffee into forest and government lands has changed the tree density and composition (Ambinakudige and Sathish, 2008), a change that ultimately resulted in land degradation. Based on the results and analysis in this study, it is clear that LULC change and land degradations are not just the consequences of household-level decisions but are a complex mixture of social, political and economic forces operating at global, regional and local levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the Western Ghats of India, agricultural expansion is seen as one of the major causes of deforestation (Menon and Bawa, 1998). The area under coffee cultivation in the Western Ghats has increased significantly in the last century and is considered to be one of the major causes of deforestation in the region (Menon and Bawa, 1998;Ambinakudige and Sathish, 2008). Coffee being a global commodity, the collapse of international coffee agreement in the 1989 significantly affected farmers' land-use decisions and livelihood outcomes throughout the coffee-growing areas in the world (Talbot, 2004;Ambinakudige, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This region is considered as a biodiversity hotspot (Ambinakudige and Sathish, 2008). Forests represent almost 50% of this landscape, and coffee estates about 30%.…”
Section: Case Study Review Coffee Agroforests In the Western Ghats Imentioning
confidence: 99%